2012
DOI: 10.5489/cuaj.10192
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit of sexual function post-radical prostatectomy

Abstract: Introduction: In the event of the implementation of prostate cancer screening, younger men will be diagnosed more frequently. Erectile dysfunction (ED) is a frequent long-term complication in men post-radical prostatectomy (RP). Since the introduction of RP, urologists have strived to improve postoperative sexual function. There is little literature, however, in the area of ED prescribing and sexual pursuit in men post-RP. We assessed the pursuit of sexual function in this group of patients. Methods: The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This hypothesis is supported by previous studies, wherein patients with high‐risk prostate cancer tended to experience psychological stress about their cancer outcome rather than their sexual activity soon after RARP 17 . Another study on sexual activity after RARP reported that patients take a long time to recover their interest in sex 18 . Another possible reason is that high expectations for SF recovery eventually caused dissatisfaction due to the naturally slow recovery of SF after RARP.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This hypothesis is supported by previous studies, wherein patients with high‐risk prostate cancer tended to experience psychological stress about their cancer outcome rather than their sexual activity soon after RARP 17 . Another study on sexual activity after RARP reported that patients take a long time to recover their interest in sex 18 . Another possible reason is that high expectations for SF recovery eventually caused dissatisfaction due to the naturally slow recovery of SF after RARP.…”
Section: Discussionsupporting
confidence: 68%
“…17 Another study on sexual activity after RARP reported that patients take a long time to recover their interest in sex. 18 Another possible reason is that high expectations for SF recovery eventually caused dissatisfaction due to the naturally slow recovery of SF after RARP. In fact, patients with higher expectations for postoperative status tend to experience regret after RARP.…”
Section: Discussionmentioning
confidence: 99%
“…Visit (mo) It has been demonstrated that, in discussing treatment options for men with localized prostate cancer, urologists rarely discuss patients' interest in sex. 29 We demonstrate the importance of the evaluation of interest and satisfaction measures over time and show that, despite preconceived notions from prior studies indicating low interest in sex after radical prostatectomy, 30 this cohort of patients had high interest in sex after radical prostatectomy with a significant increase in interest from 3 to 24 months after prostatectomy. This may indicate that as men are cured of prostate cancer, they shift their focus from survival to quality of life.…”
Section: Relationship Between Urinary Symptoms and Sexual Function Wimentioning
confidence: 54%
“…However, studies show that 24 months is the time point of optimal recovery of sexual function, 35 with rates of sexual activity in some cases peaking at 3 to 6 years after surgery. 30 It is possible that beyond 24 months, we might see changes in interest and satisfaction because there may be continued improvement in erectile function and adaptation of patients and their partners. In addition, we only evaluated these measures in patients after radical prostatectomy; they could potentially be useful in patients after other treatments for prostate cancer, including radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include outcomes beyond 24 months. Although recovery of sexual function is uncommon beyond 24 months, there is some evidence that sexual activity recovery after surgery in some cases peaks at 3–6 yr after surgery [30] , [31] . In addition, this model is only applicable to patients considering RP and does not predict sexual function following other prostate cancer treatments such as radiation therapy.…”
Section: Discussionmentioning
confidence: 99%